Effect of loading rates to the fracture toughness on carbon manganese steel ASTM 516 grade 70 / Abdullah Abd. Ghani and Mohd Fadhir Abd. Rahman - Abd. Ghani, Abdullah; Abd. Rahman, Mohd Fadhir (Faculty of Mechanical Engineering, 1996)
Material resistance to fracture or fracture toughness can be determined from experimental testing. The experimental condition in toughness measurement should relevant to the service application. Where with same fracture toughness at high loading rate is suitable to high strain application while low loading rate is useful at low strain application. The experimental technique has a major influence on design for crack growth that is unstable, fatigue and time dependent in steel that are homogeneous. The testing is according to BS 5762 : 1979 on ASTM 516 Grade 70, which is commonly used in pressure vessel structure. The test is done at room temperature, constant displacement 12 mm/s and transition load. The result is analysed for fracture toughness value determination. The result for K1C from CTOD testing is found to be invalid. Hence J integral method should be done to determined the K1C, according to the ASTM standards E813-81, " J1C , A Measure of Fracture Toughness". J1C was found 115 N/mm1'2. This value is slightly higher for such materials. This might due to the blunting ahead the notch and testing is done without precracking.